Design of Conformal Cooling of an Additively Printed Aluminium Die-Casting Mold Component - J. Sviželová; L. Socha; A. Mohamed; M. Pinta; K. Koza; T. Sellner; K. Gryc; M. Dvořák; M. Roh (Archives of Foundry Engineering)
The paper describes the design of conformal cooling of an aluminium die-casting mold component using numerical simulations along with validation under industrial conditions. The subject of modifications was the insert. The insert comes into direct contact with the metal during the filling of the mold and solidification of the casting and determines the internal shape of the casting. The aim was to optimize the operating temperatures of the insert, reduce thermal stress in the most exposed area, achieve a more even distribution of temperatures in its volume, and maintain the casting quality. Shape modifications were made by topology optimization to reduce the volume of the insert and achieve material savings. 3D printing was chosen as the production technology due to the wider possibilities regarding the variability of the shape of the internal cooling channels. Three geometric designs of the insert were created, and numerical simulations of the temperature field of the mold were carried out in ProCAST software for each variant. Numerical simulations were validated through the temperature field of the mold detected by a thermal camera during the casting cycle. Based on the results, the final design D was selected, for which a complete numerical simulation was performed, including the filling and solidification of the castings. The results were compared with the original variant A. By adjusting the cooling, temperatures were reduced in the most temperature-exposed area of the insert. The new insert variant D showed higher temperatures in the rest of the volume, resulting from material volume reduction. However, the temperatures became even, and the temperature gradients that existed in the original insert variant A were reduced. The simulation also showed that changes in the temperature field of variant D will not negatively affect the quality of the castings. The component will be manufactured and tested in operational conditions in the next research phase.